Aerobic Oxidation of Alcohols Catalyzed by V2O5 Rods Decorated on Graphene Oxide. Issue 45 (4th December 2018) - Anbu, Nagaraj; Ruby Kamalam, Maniveldoss Beaula; Sethuraman, Kunjithapatham; Dhakshinamoorthy, Amarajothi
Abstract: The present work reports the preparation of two different nanocomposites, namely, 5 wt% V2 O5 rods supported on graphene oxide (GO) (GV1) and 10 wt% V2 O5 rods supported on GO (GV2). These nanocomposites are prepared by mixing V2 O5 precursor and GO suspension with the assistance of sonication method as a non conventional source of energy. The structural features of these nanocomposites are characterized by powder X‐ray diffraction (XRD), Fourier transform‐infrared spectroscopy (FT‐IR), Raman, scanning electron microscope (SEM), transmission electron microscope (TEM), atomic force microscope (AFM) and UV‐Visible spectroscopy. These analyses confirm the existence of V2 O5 rods decorated on GO sheets. Furthermore, the catalytic activity of these nanocomposites is examined in the aerobic oxidation of benzyl alcohol under mild reaction conditions. The observed catalytic data indicate that the present experimental conditions afford complete conversion of benzyl alcohol with 100% selectivity to benzaldehyde with GV2 as a solid catalyst. On the other hand, this catalyst is also effective to promote secondary alcohol oxidation to its corresponding carbonyl compound, thus demonstrating wide substrate scope. The reusability experiments indicate that the activity is decreased in consecutive recycles in the aerobic oxidation of benzyl alcohol. On the other hand, the process is heterogeneous in nature as evidenced by hot filtration experiment. Abstract : This work describes the synthesis, characterization of V2 O5 /GO (GO: graphene oxide) nanocomposites and their activity is investigated in the aerobic oxidation of benzyl alcohol with quantitative conversion and high selectivity to benzaldehyde. Interestingly, the activity of V2 O5 /GO is much superior to GO and V2 O5 under identical reaction conditions. Some of the salient features of this work are requiring mild reaction conditions, absence of peroxides and exhibiting wide substrate scope.